COMPARATIVE ANALYSIS OF MECHANICAL PROPERTIES OF ARTIFICIAL TEETH MADE FROM VARIOUS MATERIALS IN REMOVABLE PROSTHETICS (World Bulletin of Public Health, 2025)
Today, the necessity of using complete removable prosthetics comprises 15-46% among patients aged 45 to 75 years. However, according to WHO data, 26% of patients do not use plate prostheses for various reasons, one of which is the unsatisfactory quality of artificial dentition. It should also be noted that the average service life of a plate prosthesis is about 5 years. Therefore, the task of increasing the functional value of removable prostheses remains relevant